Pengaruh Persepsi Mahasiswa UIN Banten Tentang Bank Syariah Terhadap Minat Menggunakan Produk Bank Syariah - M. Fajri Asshidiqy; Rihadatul Aisy; M. Rafli Rizky; Wahyu Hidayat (KOLONI, 2023)
This study aims to analyze the influence of students' perceptions of Islamic banks on their interest in using Islamic banking products. This factor is important because the increased interest in using Islamic bank products can provide impetus for the development of the increasingly rapid Islamic banking industry. This research uses a quantitative approach with survey methods and data collection is done through a questionnaire. The research sample consisted of 100 students from various study programs at UIN Banten who have access to Islamic banking services. The collected data were analyzed using multiple linear regression analysis. The results of this study indicate that perceptions about bank interest and perceptions about the profit-sharing system have a positive and significant influence on the intention to use Islamic bank products.  Keywords: Perceptions about bank interest, Profit sharing system Islamic banking products